Answer:
Cylindrical:
5r^2(sin(t)^2 - cos(t)^2) +r(3cos(t) + 5sin(t)) - 3z^2 + 4z + 12 = 0
Spherical:
5r^2sin(t)^2 (sin(f)^2 - cos(f)^2) - 3r^2 cos(t)^2 + r sin(t) (3cos(f) + 5sin(f)) + 4r cos(t) +12 = 0
Explanation:
In cylindrical coordinates:
x = r cos(t)
y = r sin(t)
z = z
Let us reorganize the original equation
−5x^2+3x+5y^2+5y−3z^2+4z+12=0
5 (y^2-x^2) + 3x + 5y - 3z^2 + 4z + 12 = 0
Now, we can replace x and y:
5 (r^2 sin(t)^2 - r^2 cos(t)^2) + 3rcos(t) + 5r sin(t) - 3z^2 + 4z + 12 = 0
5r^2(sin(t)^2 - cos(t)^2) +r(3cos(t) + 5sin(t)) - 3z^2 + 4z + 12 = 0
In spherical coordinates:
x = r sin(t) cos(f)
y = r sin(t) sin(f)
z = r cos(t)
Let us reorganize the equation:
5 (y^2-x^2) - 3z^2 + 3x + 5y + 4z + 12 = 0
5r^2sin(t)^2 (sin(f)^2 - cos(f)^2) - 3r^2 cos(t)^2 + r sin(t) (3cos(f) + 5sin(f)) + 4r cos(t) +12 = 0